Legal Actions of Polri Investigators Against the Criminal Action of Environmental Damage - Badrunsyah Badrunsyah; Mona Minarosa (Budapest International Research and Critics University, 2022)
The maintenance of the sustainability of environmental functions is intended for the benefit of the wider community. Therefore, it takes responsibility, openness, and community participation, so as to maintain and increase the carrying capacity and capacity of the environment, it becomes the basis for sustainable development. For this reason, Indonesia's environment must be managed with the principle of preserving harmonious, harmonious and balanced environmental functions to support sustainable development with an environmental perspective for increasing welfare and prosperity. On another aspect, while there is still abuse by legal entities, businesses carry out their business activities by logging forests through environmental destruction while at the same time increasing environmental damage. This is certainly a violation based on the provisions of Law Number 32 of 2009 concerning Environmental Protection and Management. The problem is; What are the legal actions of Polri investigators against perpetrators of environmental destruction that are strongly suspected of being carried out by corporate legal entities according to Law Number 32 of 2009 concerning Environmental Protection and Management. Research Methods In order to solve this research, the authors conducted a normative legal research approach.Research results and discussion; That in essence, the legal action that must be taken by Polri investigators against perpetrators of environmental destruction by a corporate legal entity who is strongly suspected of violating Law Number 32 of 2009 concerning Environmental Protection and Management, is to take legal action based on the provisions stipulated by the Criminal Procedure Code, which begins with conducting an investigation within the framework of the formulation of a criminal act as regulated under Law Number 32 of 2009 concerning Environmental Protection and Management. Furthermore, based on the results of the investigation related to the alleged case, the investigation was carried out to upgrade the status to an investigation, in order to ensure that there are parties responsible for the existence of legal entities that are considered to have committed acts of environmental destruction and their impacts. If a party is deemed to have fulfilled the elements, then that party can be made a suspect for the perpetrators of environmental destruction.